Babayi kag kalalat-an a look into the experiences of women in Barangay La Paz a decade after the 2006 Guimaras oil spill. - Robles, Arielle Lois Coo (2017.)
The M/T Solar oil spill that happened ten years ago off the southern coast of Guimaras has not only damaged the ecosystem of the province but also affected the lives of its residents, especially the women. My study aimed to look into the experiences of women living in Barangay Lapaz, Nueva Valencia, Guimaras, one of the highly-affected areas in the province, following the oil spill. I also looked into the disaster recovery activities that these women engaged in for the benefit of their household and community recovery. Using Feminist political ecology as the framework of this study, I gathered data by conducting key informant interviews to women who has been chosen through purposive non-random sampling based on their characteristics. The collected data was then analyzed. The results were then categorized according to the following: experiences prior to and after the oil spill, their reproductive and productive activities, the reproductive and productive activities they engaged in for the recovery of their household, and the economic and environmental activities that these women participated in for the recovery of their community. From the findings, I learned that the oil spill affected the source of livelihood of these women that they ventured into domestic labor in order to provide for their families, they had to be relocated. Moreover, I also learned that the participants experience multiple burden due to their struggle with balancing their reproductive and productive roles. Grounding on findings, I concluded that these women had different experiences when it came to disaster recovery and the effects of the oil spill however, they displayed resilience despite their vulnerabilities and took on more roles and responsibilities which epitomized women?s place in the political ecology as users and managers of the environment. Finally, with my study?s scope and limitations as bases, I made recommendations that Barangay Lapaz can use that could benefit the women in their community when disaster strikes.
Research (Undergraduate, Bachelor of Arts in Political Science-History) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Oil spill -- Guimaras; Women -- Barangay Lapaz, Guimaras; Guimaras Oil Spill -- 2006.